Preparation of Fucoidan from Laminaria japonica by Ethanol-free Extraction Process - Yanhong CHEN; Yuting DONG; Pengjie CHUAI; Shiqiaoxin CHEN; Zedong JIANG; Yanbing ZHU; Hui NI; Shanggui DENG; Qingbiao LI (Shipin gongye ke-ji, 2022)
In this study, based on the traditional hot water extraction-ethanol precipitation method for fucoidan, the ethanol-free extraction process of kelp fucoidan was studied in accordance with the difference in the fucose contents and sulfate groups of fucoidans and their beneficial biological activities. Three extraction methods including hot water extraction-ethanol precipitation method, hot water extraction-acid precipitation method, and hot water extraction-acid precipitation-enzymatic hydrolysis assisted extraction method, were applied to prepare fucoidans, and three fucoidan samples (sample 1, sample 2 and sample 3) were obtained, respectively. Fucose and sulfuric acid group-contents and biological activities (antioxidant, antibacterial activities) analysis results showed that the contents of fucose and sulfate groups in fucoidan (sample 3) prepared by hot water extraction-acid precipitation-enzymatic assisted hydrolysis method were 41.10%±0.87% and 24.90%±0.15%, respectively, which were significantly higher than the Trade Standard requirements of fucoidan (SC/T 3404-2012), samples 1 and sample 2. Meanwhile, the sample 3 also had the best antioxidant and antibacterial activities in three fucoidan samples. The Response surface methodology (RSM) was used to optimize the key process conditions of hot water extraction-acid precipitation-enzymatic hydrolysis assisted extraction of fucoidan. The best extraction process parameters were obtained as follows: Extraction temperature was 90℃, extraction time was 2.0 h, liquid material ratio was 40:1 mL/g, and the extraction yield reached 9.65%±0.11%. In this study, raction rate of fucoidan and the biological activity of fucoidan prepared by hot water extraction-acid precipitation-enzymatic assisted hydrolysis method were significantly higher than those prepared by hot water extraction-ethanol precipitation method and hot water extraction-acid precipitation method, therefore, the hot water extraction-acid precipitation-enzymatic assisted hydrolysis method digestion would be a good process to effectively replace the hot water extraction-ethanol precipitation method for fucoidan extraction.